Investigating the Relationship between Serum Glucose and Inflammatory Markers in Diabetic Rats with Progressive Resistance Exercise - Maryam Vatandoust; Ali Zare (Fasa University of Medical Sciences, 2021)
Background & Objective: Diabetes Mellitus (DM) is a condition that is associated with an increase in inflammatory markers and studies show that resistance exercise with appropriate intensity can reduce inflammation generally. The aim of this study was to investigate the relationship of serum glucose with Interlekin18 (IL-18) and Tumor Necrosis Factor-alpha (TNF-α) in Diabetic rats with progressive resistance exercise. Materials & Methods: In this experimental study, 32 Wistar male rats were distributed to sedentary control, trained control, sedentary diabetic, and trained diabetic groups of 8. Diabetes was induced by Streptozotocin (55 mcg/bw-i.v.). The resistance training protocol consisted of elevating upward from a ladder with weight, supporting an overload equivalent to 5% of body weight, during 6 weeks. The data obtained were analyzed by ANOVA and Tukey's posthoc multiple comparison tests, and a significance level of 5% was considered. Results: According to results, serum concentrations of TNF-α and IL-18 decreased significantly in trained diabetic group compared to sedentary diabetic group after resistance training. While in the amount of TNF-α in the trained control group compared to the sedentary control group, a significant increase was observed, and in the amount of IL-18 in trained control group compared to the sedentary control group, a significant decrease was observed. But regarding the correlation between serum IL-18 concentration and glucose, only in sedentary control group, a significant correlation was observed. Conclusions: Resistance training was able to reduce TNF-α and IL-18 inflammatory markers in trained diabetic rats and improve metabolic and immune aspects in diabetes mellitus.